Quality of life and associated factors in type 2 diabetes mellitus: a cross-sectional study - Santos, Soraia (2015)
Introduction: Type 2 diabetes mellitus (DM) has high social and economic costs. It is often associated with decreased quality of life (QoL). Objectives: To assess the impact of demographic and clinical factors on QoL in a sample of patients with DM type 2. Study type: Cross-sectional study. Setting: Espinho FHU. Population: Patients with DM type 2 followed by the Espinho Family Health Unit in December of 2012. Methods: A convenience sample of 231 patients visiting the FHU for a DM consultation was selected. Demographic and clinical data were collected and the Diabetic Health Profile questionnaire was applied to evaluate QoL. The association of continuous variables with DHP dimensions was assessed using the Pearson correlation coefficient and the influence of categorical variables was tested with the Student t-test and ANOVA. Results: Female gender, lower educational level, severe hypoglycemia, and microvascular complications had a negative impact on the ‘psychological distress’ dimension of QoL. ‘Barriers to activity’ were negatively associated with insulin therapy and severe hypoglycemia. Patients with lower educational level and without glycemic control had lower QoL with regard to ‘disinhibited eating’. Conclusions: QoL is a complex concept with multiple determinants. It is important to study these factors and assess them in each patient with DM for more effective intervention.